A cluster randomized controlled trial evaluating the effectiveness of the school‐based drug prevention program #Tamojunto2.0. (28th January 2021) - Sanchez, Zila M.; Valente, Juliana Y.; Galvão, Patricia P.; Gubert, Fabiane A.; Melo, Márcia H. S.; Caetano, Sheila C.; Mari, Jair J.; Cogo‐Moreira, Hugo
ABSTRACT: Aims: The study aimed to evaluate the effectiveness of the government school‐based program #Tamojunto2.0, the third Brazilian version of the European drug prevention program, Unplugged, in preventing the use of alcohol and other drugs. Design: A parallel, two‐arm cluster randomized controlled trial was conducted in 205 classes in 73 public schools (37 intervention and 36 control) with a baseline assessment and follow‐up after 9 months. Setting: Schools in the cities of São Paulo, Fortaleza and Eusebio in Brazil. Participants: A total of 5208 students in the 8th grade with a mean age of 13.2 years (standard deviation = 0.8 years) and an equal gender ratio. Intervention: In 2019, the intervention group attended 12 classes of the program #Tamojunto2.0, under the supervision of a team from the Ministry of Health. The control group did not receive any intervention to prevent alcohol and drug use. Measurements: The primary outcome measured was prevalence of binge drinking (five or more doses of alcohol in an occasion) within the past month. Secondary outcomes were prevalence of initiation and use of alcohol, tobacco, inhalants, marijuana and cocaine within the past month. Findings: A statistically significant difference was not found in the prevalence of binge drinking within the past month between intervention and control groups [odds ratio (OR) = 0.934; 95% confidence interval (CI) = 0.761–1.146]. However, students who were exposed to the program were less likely to initiate alcohol use than those in the control group (OR = 0.782; 95% CI = 0.636–0.961). The Bayes factor for reduction in binge drinking was 0.01, providing evidence in favor of the null hypothesis for this variable. Conclusions: The drug prevention program #Tamojunto 2.0 reduced alcohol initiation, but appeared not to reduce past‐month binge drinking among 8th grade students in Brazil.